Resepsi Hadis-Hadis Misoginis dalam Perspektif Ikatan Pelajar Muhammadiyah di Kapanewon Depok Yogyakarta - Hidayah, Saniatul; Rifai, Idris Ahmad (Journal of Hadith Studies, 2024)
In contemporary social reality, misogynistic thought is not only gaining strength across various levels of society but is also developing dynamically among students. This discourse often emerges through textual interpretations of hadiths which, often unconsciously, have the potential to discredit women. In response to this tendency, Muslim feminist scholars such as Fatima Mernissi have proposed alternative methods for reading hadiths perceived as misogynistic. Therefore, studying the reception of misogynistic hadiths becomes crucial, especially within Islamic student organizations such as Ikatan Pelajar Muhammadiyah (IPM), to emphasize that hadith studies continue to evolve in line with contemporary contexts. This research seeks to answer two main questions: how is the reception of misogynistic hadiths manifested among IPM members, and what factors underlie the formation of those reception patterns. This study adopts a qualitative field research approach using Focus Group Discussions and interviews as data collection methods. The analysis employs Stuart Hall’s reception theory, which posits that meaning is not fixed but is constructed through the interaction between the text and the reader, shaped by their social, cultural, and personal backgrounds. Based on the analysis of four selected hadiths concerning female leadership, women invalidating prayer, women entering hell because of a cat, and women as sources of misfortune the findings reveal that the majority of IPM members (75%) adopt a contextual (oppositional) reading, while a smaller portion (25%) engage in a textual (dominant) reading. These patterns of reception are influenced by the socio-cultural dynamics present within their organizational and educational environments.